Genome-scale networks link neurodegenerative disease genes to alpha-synuclein through specific molecular pathways - Khurana, Vikram (Cell Syst, 2017)
Numerous genes and molecular pathways are implicated in neurodegenerative proteinopathies, but their inter-relationships are poorly understood. We systematically mapped molecular pathways underlying the toxicity of alpha-synuclein (α-syn), a protein central to Parkinson’s disease. Genome-wide screens in yeast identified 332 genes that impact α-syn toxicity. To “humanize” this molecular network, we developed a computational method, TransposeNet. This integrates a Steiner prize-collecting approach with homology assignment through sequence, structure and interaction topology. TransposeNet linked α-syn to multiple parkinsonism genes and druggable targets through perturbed protein trafficking/ER quality control and mRNA metabolism/translation. A calcium signaling hub linked these processes to perturbed mitochondrial quality control/function, metal ion transport, transcriptional regulation and signal transduction. Parkinsonism gene interaction profiles spatially opposed in the network (ATP13A2/PARK9, VPS35/PARK17) were highly distinct, and network relationships for specific genes (LRRK2/PARK8, ATXN2 and EIF4G1/PARK18) were confirmed in patient iPS cell-derived neurons. This cross-species platform connected diverse neurodegenerative genes to proteinopathy through specific mechanisms, and may facilitate patient stratification for targeted therapy.